INNOVATION IN UTILIZING INFORMATION TECHNOLOGY SYSTEMS IN IMPROVING THE QUALITY OF NURSING SERVICES: DOI: https://doi.org/10.35654/ijnhs.v1i2.27 - Ahmad Dahlan Sayam; Sukihananto Sukihananto (Alta Dharma Publisher, 2018)
Background: Advances in technology in the field of health are increasingly increasing, enabling everyone to use existing technology. Today, advances in information technology that allow for the development of professional nursing services, and the attention of current epidemiology and sociodemography, are very important for nurses. to become familiar with health information systems Methods: The conceptual framework proposed was to look at the theory and empirical literature used in nursing studies and its benefits, which were reviewed from several research results from 2013 to 2018. This study used 17 journals that were reviewed against it. Results: Several innovations in the field of information technology in the field of nursing have been developed and evaluated for its benefits. Based on what is in the literature in this article, Nurse Calling Systems (NCSS), EHR and CDSS, MDTT, computers and infusion management systems are a number of innovations that have been developed for developing technology to provide better quality services. The benefits obtained when using these innovations, namely more efficient management, more effective use of costs, improved planning programs, increased utilization of nurses. The benefits of information systems in nursing more time with, patients and less time in station nurses, reducing the use of paper nursing care automatically the same standard in care (nursing process) reduce the cost of nursing services can be measured Conclusion: it takes several innovations in the field of nursing that have been widely applied, which are carried out on benefits that provide enormous benefits in the practice of nursing services. So it is recommended that in the future Indonesia can implement innovations that can help improve nurse performance in Indonesia according to existing needs Keywords: Innovation, Nursing Information System, Benefits